A case of Coffin–Lowry syndrome with premature exfoliation of primary teeth - K. IGARI, Y. HOZUMI, Y. MONMA, & H. MAYANAGI (Paediatric Dentistry, 2006)
We present a case of a 5-year-old boy with premature exfoliation of primary teeth. All eight primary incisors had exfoliated by the age of 3 years, and three canines and one primary first molar were subsequently lost when he was 4 years old. None of the exfoliated teeth exhibited caries.